Effectiveness of STAD (Student Team Achievement Division) Cooperative Learning Method to Improve Students' Cognitive Learning Outcomes - Panji Prasetya Utama; Munirul Abidin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Teacher centered learning often makes the learning atmosphere less varied resulting in low participation in the learning process, especially in an environment that has limited use of digital media at Pondok Muhammadiyah Boarding School, so that students' Arabic cognitive learning outcomes are low. The purpose of this study was to determine the effectiveness of the STAD type (Students Team Achievement Devision) cooperative learning method on Arabic cognitive learning outcomes of grade XI students at MBS Muhammadiyah Jetis Ponorogo boarding school. The method used in this research is quantitative with a quasi-experiment approach. The sample in this study consisted of 26 students of class XI. Data collection was carried out through observation and test techniques including pre-test and post-test, then the data was analyzed using descriptive statistical tests, normality tests, and T tests. The findings demonstrated that the experimental class learning outcomes' Sig value had a significance value > 0.05 in other words, the data showed a normal distribution, this indicates that STAD cooperative learning can improve students' cognitive learning outcomes compared to conventional learning methods.